Cervical Alignment Changes in Patients Developing Proximal Junctional Kyphosis Following Surgical Correction of Adult Spinal Deformity. Issue 4 (12th October 2017) - Passias, Peter G; Horn, Samantha R; Jalai, Cyrus M; Ramchandran, Subaraman; Poorman, Gregory W; Kim, Han Jo; Smith, Justin S; Sciubba, Daniel; Soroceanu, Alexandra; Ames, Christopher P; Hamilton, D Kojo; Eastlack, Robert; et al.
Abstract: BACKGROUND: Proximal junctional kyphosis (PJK) following adult spinal deformity (ASD) surgery is a well-documented complication, but associations between radiographic PJK and cervical malalignment onset remain unexplored. OBJECTIVE: To study cervical malalignment in ASD surgical patients that develop PJK. METHODS: Retrospective review of prospective multicenter database. Inclusion: primary ASD patients (≥5 levels fused, upper instrumented vertebra [UIV] at T2 or above, and 1-yr minimum follow-up) without baseline cervical deformity (CD), defined as ≥2 of the following criteria: T1 slope minus cervical lordosis < 20°, cervical sagittal vertical axis < 4 cm, C2-C7 cervical lordosis < 10°. PJK presence (<10° change in UIV and UIV + 2 kyphosis) and angle were identified 1 yr postoperative. Propensity score matching between PJK and nonPJK groups controlled for baseline alignment. Preoperative and 1-yr postoperative cervical alignment were compared between PJK and nonPJK patients. RESULTS: One hundred sixty-three patients without baseline CD (54.9 yr, 83.9% female) were included. PJK developed in 60 (36.8%) patients, with 27 (45%) having UIV above T7. PJK patients had significantly greater baseline T1 slope in unmatched and propensity score matching comparisons ( P < .05). At 1 yr postoperative, PJK patients had significantly higher T1 slope ( P < .001), C2-T3 Cobb ( P = .04), and C2-T3 sagittal vertical axis ( P = .02). New-onset CD rate in PJK patients was 15%, and 16.5% in nonPJK patients ( P > .05). Increased PJK magnitude was associated with increasing T1 slope and C2-T3 SVA ( P < .05). CONCLUSION: Patients who develop PJK following surgical correction of ASD have a 15% incidence of development of new-onset CD. Patients developing PJK following surgical correction of ASD tend to have an increased preoperative T1 slope. Increased progression of C2-T3 Cobb angle and C2-T3 SVA are associated with development of PJK following surgical correction of thoracolumbar deformity.